ANALISIS PERBANDINGAN KINERJA KEUANGAN PEMERINTAH DAERAH DI JAWA TIMUR SEBELUM DAN SETELAH PENERAPAN ACCRUAL BASED - PRIYO ATMOJO, DWI (Jurnal Akuntansi AKUNESA, 2017)
This study was aimed to analyze the comparation of local government?s financial performancebefore using accrual basis and after using accrual basis in East Java Local Governmentas measured by level of financial independence. The result of kolmogorov-smirnov showed that the data are not normally distributed, so the hypothesis testing using wilcoxon signed rank test and showed that there are significantly different between local government?s financial performance before and after using accrual basis. The result support Peraturan Pemerintah Nomor 71 Tahun 2010?s state about one of the purpose using accrual basis is for performance evaluation. Then the view of agency thery showed that accrual basis more useful for principal. From the view of stakeholder theory, accrual basis is an government?s effort to increase their performace through a favorable report to stakeholder and from the view of decision usefulness theory, the financial report using accrual basis is more valuable for users.